Genetically predicted levels of folate, vitamin B12, and risk of autoimmune diseases: A Mendelian randomization study - Yang, Hong; Song, Jie; Li, Aole; Lv, Linshuoshuo; Sun, Xiaohui; Mao, Yingying; Ye, Ding (Frontiers in Immunology, 2023)
Background: Evidence from observational studies on the association of folate and vitamin B12 with autoimmune diseases are conflicting. Objective: We aimed to investigate the relationship of folate and vitamin B12 with autoimmune diseases using Mendelian randomization (MR). Materials and Methods: We selected single nucleotide polymorphisms associated with folate and vitamin B12 at the genome-wide significance level. Summary-level data for four common autoimmune diseases (vitiligo, inflammatory bowel disease, rheumatoid arthritis, systemic lupus erythematosus) were obtained from large-scale genome-wide association studies, with the sample size of 44266,86640,58284 and 23210, respectively. MR analyses were conducted using the inverse variance weighted (IVW) approach, and sensitivity analysis were further performed to test the robustness. Results: We found that higher genetically determined serum folate level per one standard deviation (SD) was associated with decreased risk of vitiligo by the IVW method (odds ratios [OR] =0.47;95% confidence interval [CI]:0.32-0.69; P = 1.33×10-4). Sensitivity analyses using alternative methods showed similar associations, and no evidence of pleiotropy was detected by MR-Egger regression (P = 0.919). In addition, we observed that vitamin B12 per one SD was positively associated with IBD (IVW: OR = 1.14, 95% CI: 1.03-1.26, P = 0.010; maximum likelihood: OR = 1.14, 95% CI: 1.01-1.29, P = 0.035; MR-PRESSO: OR = 1.14, 95% CI:1.01-1.28, P =0.037), while the association was not significant after Bonferroni correction. Conclusion: The study provides convincing evidence for an inverse association between serum folate level and risk of vitiligo. Further studies are warranted to elucidate the possible association between vitamin B12 and risk of IBD.